2017
DOI: 10.1182/bloodadvances.2016001842
|View full text |Cite
|
Sign up to set email alerts
|

T-cell assays confirm immunogenicity of tungsten-induced erythropoietin aggregates associated with pure red cell aplasia

Abstract: • Tungsten-induced rhEPO aggregates in clinical lots are associated with rhEPOneutralizing antibodies and PRCA.• T-cell responses differentiate nonaggregated from aggregated rhEPO, confirming immunogenicity of tungsten-induced rhEPO aggregates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…The second case affected a biosimilar epoetin [35,36]. A comparative efficacy study, undertaken to complete the data package for gaining approval for subcutaneous (SC) treatment of chronic kidney disease patients, was stopped in 2009 after two patients developed neutralizing antibodies.…”
Section: Evaluation Of Comparative Efficacy Studiesmentioning
confidence: 99%
“…The second case affected a biosimilar epoetin [35,36]. A comparative efficacy study, undertaken to complete the data package for gaining approval for subcutaneous (SC) treatment of chronic kidney disease patients, was stopped in 2009 after two patients developed neutralizing antibodies.…”
Section: Evaluation Of Comparative Efficacy Studiesmentioning
confidence: 99%
“…Cell-based models presented in the previous section highlighted that aggregated antibodies could fulfill the two latter activation signals. However, the role of aggregates in the initiation of a specific T-cell response has been less explored (62), even though the specificity of the immune response to native monoclonal antibodies has been well documented over the past years, as described hereafter.…”
Section: Antibody Aggregates and The Generation Of De Novo Antigensmentioning
confidence: 99%
“…How could aggregation modulate the specific T-cell response detected for native antibodies? One study exploring the T-cell response to erythropoietin and heat-or tungsten-induced erythropoietin aggregates in an autologous moDC-T-cell coculture model that aggregates induced an increase in T-cell proliferation compared to native erythropoietin (62). This is the only study to date evaluating the specific T-cell activation in response to BP aggregates.…”
Section: The Role Of Antibody Aggregates In the Initiation Of A Specimentioning
confidence: 99%
“…SC use of the reference medicine was subsequently re-instated, allowing such a study to be conducted; however, two patients developed neutralizing anti-erythropoietin antibodies following SC administration of HX575 in this trial. 14 Results of a thorough root–cause analysis indicated that atypical increased tungsten levels in pre-filled syringes precipitated immunogenic reactions with two batches of the study medication; 15 , 16 the manufacturing process of the syringe barrels was subsequently changed to consistently reduce the tungsten levels to specified low levels (introduction of low-tungsten syringes).…”
Section: Further Clinical Development and Recent Ema Approval Of Sc Hmentioning
confidence: 99%